Computational modeling of drug diffusion and inductive heating in an implantable biomedical device for localized thermo-chemotherapy of cancer cells/tissue. Issue 1 (1st January 2018) - Ani, C.J.; Danyuo, Y.; Odusanya, O.S.; Soboyejo, W.O.
Abstract: This paper presents the study of an implantable biomedical device for the localized released of chemotherapeutic drugs and the controlled heating of surrounding tumor tissue to enable cancer treatment via a hyperthermia and chemotherapy combination. The coupling of magnetic induction, heat transfer, and mass diffusion concepts used to model temperature changes and drug release from the biomedical device to a surrounding environment that mimics breast tumor tissue and normal breast tissue. The predictions of temperature change in the residual tumor cells and the normal breast tissue show that when an excitation current of 25 mA supplied to the device generates heat that required to kill the residual cancer cells without damaging the nearby healthy tissue. Also, the predictions of prodigiosin concentration released from the biomedical device into selected depths in the breast phantom model show that the residual tumor has a higher concentration than the healthy tissue. The proposed system proved capable for prolonged drug delivery and temperature rise of tumor to therapeutic values for effective localize cancer treatment.